Sistem Pemadam Api Berbasis Internet of Things (IoT) dengan Integrasi Aplikasi Telegram - Farid Muhammad Hadji; Muhammad Reihan Daffa Putra; Rizky Ade Kusuma; Ayu Mawadda Warohma (Universitas Multi Data Palembang, 2026)
Residential fires are critical incidents that often result in severe material losses and casualties due to delayed detection and manual mitigation limitations. This study aims to design an Internet of Things (IoT)-based fire extinguishing system integrated with the Telegram application. The system utilizes an ESP32 microcontroller as the main processing unit, connected to a DHT11 temperature sensor, MQ-2 smoke sensor, and Flame Sensor. The research methodology involves hardware prototyping and implementing automatic control logic. The results demonstrate that the system successfully detects fire and smoke in real-time. Specifically, the Flame Sensor showed a rapid response time of 1.15 seconds, while the MQ-2 sensor detected smoke within 3.18 seconds. Upon detecting fire, the system automatically activates a 12V mini pump via a relay to simulate fire suppression and simultaneously sends immediate alert notifications to the user's smartphone via Telegram. This integrated solution offers a reliable rapid response mechanism to minimize fire damage.